Effectiveness of School-Based Interventions for Students with ADHD: A Systematic Review - Kurnia, Edo; Muluk, Marlina (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition that affects children’s and adolescents’ ability to maintain attention, regulate impulses, and control hyperactivity, often resulting in academic underachievement and behavioral difficulties in classroom settings. This systematic review synthesizes empirical evidence on school-based interventions for students with ADHD using PRISMA guidelines and the STAR framework. A comprehensive search was conducted across Scopus, ScienceDirect, Web of Science, and Google Scholar for publications between 2015 and 2025. Ten studies met the inclusion criteria, comprising randomized controlled trials, quasi-experimental designs, single-case studies, and meta-analyses. Data were analyzed using a structured narrative synthesis and effect size comparison where available. The findings show that behavioral, academic, and multimodal interventions consistently improve attention, reduce disruptive behavior, and enhance academic outcomes, with reported effect sizes ranging from d = 0.20 to 3.61. Successful implementation was strongly associated with structured teacher training and parental collaboration, while major barriers included limited time and insufficient institutional support. The review highlights the need for sustainable school-based intervention models supported by capacity building and technology-enhanced delivery. School-based interventions therefore represent a promising pathway to support improved learning and behavioral functioning among students with ADHD